Edukasi Kesehatan Tentang Hipertensi Pada Lansia Di Dusun I Desa E Wonokerto Kec. Tugumulyo Kab.Musi Rawas - Ise Lestari; Rahmawati, Yeni; Yanti, Yumi; Habibi, Julius (Jurnal Pakar Pengabdian Kesehatan, 2025)
Hypertension or high blood pressure is one of the most dangerous health problems throughout the world. Hypertension is also a major risk factor for cardiovascular disease such as heart attack, heart failure, stroke and kidney disease. Hypertension is estimated to cause 7.1 million deaths or approximately 13% of all deaths in the world. According to the World Health Organization (WHO), almost half of heart attack cases are triggered by hypertension or high blood pressure. Most high blood pressure occurs in the older generation (elderly) due to physiological and pathological changes with increasing age. Therefore, it is very necessary to prevent and maintain the quality of life of the elderly to avoid hypertension. especially in the area of ​​Hamlet 1, E Wonokerto Village which is affected by lack of knowledge and lack of healthy lifestyle. The 2025 Thematic Community Service Program (KKN-T) of Dehasen University Bengkulu focuses on efforts to prevent hypertension through an educational approach, namely with the method of hypertension counseling, implementation of good eating patterns and elderly gymnastics and distribution of leaflets. This activity was carried out through collaboration with village officials and the local community. The results of the activity showed an increase in public awareness regarding the importance of knowledge and regular treatment for hypertension sufferers. This program has proven effective as a community-based promotive and preventive strategy that can be a model for implementation in other areas. Cross-sector collaboration and ongoing education are very important to support efforts to reduce the incidence of hypertension. The method used is to conduct health education with counseling media using Leaflets to increase the knowledge of the elderly about hypertension. The results of this Community Service activity concluded that the understanding of the Elderly about hypertension has increased both in terms of understanding hypertension, causes of hypertension, signs and symptoms of hypertension, prevention of hypertension, and treatment of hypertension and handling of hypertension. At first, the elderly only knew in general, now the elderly understand it more deeply so that they can carry out prevention and treatment routinely at the Community Health Center to maintain a healthier and better quality of life in their old age.